Influence of social entrepreneurship in organizations, family, and society : causes and solutions for success - Mercader-Pomarón, Victor Manuel (My University, 2017)
The purpose of this research is to identify and analyze the need, the causes of inadequate performance, and the possible solutions applicable to Social Entrepreneurship in enterprises/organizations, families, and society. There was developed and applied an instrument to a sample of professionals working in the industrial Baja California state of Mexico, border with the state of California, United States. The responses obtained were categorized and taxonomies were created referred to organizations, families, and society which help summarize and prioritize the answers which are applicable to different types of leaders, entrepreneurs, students, educators, researchers and people in general, generating an impact for better performance.
American Journal of Management
Keywords: Social Entrepreneurship; Influence